Water level data of mdm trail 7 from the Mendaram peat swamp in Brunei Darussalam - Alexander R Cobb; Charles Franklin Harvey (PANGAEA, 2019)
Water level data were obtained from logging pressure transducers (Solinst Levelogger Edge 3001, Solinst Canada, Georgetown, Ontario, Canada) corrected for barometeric fluctuations using a barometer (Solinst Barologger Gold 3001). Each transducer was suspended on a steel cable inside a 2" PVC pipe 1.5 m in length installed to 1.4 m depth and screened at 1.3–1.45 m below the top of the piezometer casing. Piezometers were developed prior to measurement by repeatedly plunging and removing a solid rod into the piezometer tube. The details of how the surface datum was obtained are described in Cobb et al (2017, doi:10.1073/pnas.1701090114).
In supplement to: Cobb, AR; Harvey, CF (2019): Scalar Simulation and Parameterization of Water Table Dynamics in Tropical Peatlands. Water Resources Research, 55(11), 9351-9377, https://doi.org/10.1029/2019WR025411